Perancangan Sistem Informasi Perusahaan Jasa Pembuatan Akta Notaris Berbasis Web Di PT. Sariko Alam Nusantara Kota Tangerang Menggunakan Metode Extreme Programming - Agus Maulana; Ny. Ayni Suwarni Herry (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Companies that are engaged in service that intend to assist the community in facilitating the process of making the management of the legality deed of the company such as the establishment of a PT (limited company), the establishment of a CV (Commanditaire Vennootschap), the establishment of a foundation, the establishment of a cooperative and other legal activities. In practice, this reporting system is deemed ineffective. There are problems regarding the recording of clients who order the deed which is still recorded in the order book manually. So that in terms of recording errors often occur in writing. The next problem regarding the process to introduce their products or services is still with brochures so that they are not comprehensive. Therefore, a web-based information system has been created for a notarial deed service company at PT. Sariko Alam Nusantara, Tangerang City, this application website uses the Extreme Programming method as a system development method. And MySQL as a database and programming language using PHP (Hypertext Preprocessor) and CSS (Cascading Style Sheet). In this system the company can do administration, report information, regarding ordering and introduce products or services for making a notary deed to the general public or prospective clients, so that it will make it easier to monitor service order reports and make it easier for clients who will make legal permits for their companies to place orders for deed. notaries and other legal permits quickly, easily and safely.